Android mobile health application (mHealth) system - Mujere, Mecury (Midlands State University, 2018)
The purpose of this study was to come up with a Mobile health (m-Health) application system. This system allows patients’ to communicate directly via an android mobile system through notifications or messages and at the same time enables them to perform electronic booking of appointments, receive e-prescription and accessing after visit summaries from the hospital or clinic. The development of this system comes out after the identification of numerous problems which are associated with the current system. The different types of information gathering techniques were used to unveil these problems. Techniques which were used are interviews, questionnaires and observations. The results obtained shed light that there is need of a new system in the organization. This system was developed using Android and Php, after it was implemented the system was reviewed to check whether it is performing up to standard, the results from the users were positive which means it was successful. To conclude, Android mobile health system (m-health) was greatly appreciated at the organization, this at the same time calls for the future advancement of the system.